ZTA ceramic interbody fusion cage and preparation method and application thereof
By using calcium-magnesium silicate mineral/ZTA composite ceramic materials and photocuring 3D printing technology, an intervertebral fusion device with gradient porous structure was prepared, which solved the clinical problems caused by material mismatch in the prior art, and achieved personalized matching and biological activity improvement.
Patent Information
- Application Number
- CN202311083271.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-28
AI Technical Summary
Existing intervertebral fusion device materials cannot fully match individual cervical anatomical characteristics, resulting in mismatch and clinical complications such as prosthetic displacement, ectopic ossification and subtraction.
The intervertebral fusion device is prepared using calcium-magnesium silicate mineral/ZTA composite ceramic material. Through the dense outer wall and the gradient porous structure inside the porous, combined with photocuring 3D printing technology, personalized mechanical performance regulation and biological activity improvement are achieved.
The personalized matching of intervertebral fusion devices is achieved, which improves biocompatibility and mechanical properties, reduces the occurrence of clinical complications, and promotes bone repair and osteogenesis.
Smart Images

Figure CN119523693A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a ZTA ceramic intervertebral fusion device and a preparation method and application thereof, belonging to the technical field of load-bearing orthopedic implant preparation. Background Art
[0002] The current prevalence of cervical spondylosis in my country is 3.8% to 17.6%, and it is increasing year by year. Among them, shoulder and neck pain has become the second most common pain in the whole body, accounting for 28.39%. For this severe cervical degenerative disc disease accompanied by radiculopathy or myelopathy, anterior cervical discectomy and fusion (ACDF) is the preferred surgical treatment. The operation aims to stabilize the decompressed segment and promote bone tissue growth by implanting an intervertebral fusion device to achieve bone fusion. Therefore, from a biomechanical point of view, the intervertebral fusion device used in ACDF should provide long-lasting stability for intervertebral bone integration, restore the normal physiological curvature of the vertebral body, and minimize the impact on the biomechanics of adjacent segments.
[0003] There are differences in cervical spine characteristics among different races and regions. At present, intervertebral fusion devices are generally mass-produced according to molds, which do not fully conform to the anatomical characteristics of each person's cervical spine, resulting in frequent mismatch of intervertebral fusion devices, and even side effects on the effect of fusion surgery. In addition, in the long-term follow-up of ACDF surgery, a variety of clinical complications such as prosthesis displacement, heterotopic ossification, and subsidence were recorded due to mismatch of intervertebral fusion device design, size, and mechanics. In this context, it is an urgent and important task to develop an artificial cervical disc fusion device that meets the biomechanical properties and anatomical characteristics of the cervical endplate.
[0004] At present, intervertebral fusion materials include metal materials, polymer materials and ceramic materials. However, the functions that intervertebral fusion devices need to meet require material properties, such as biocompatibility, mechanical properties, and osteoinduction properties. Metal materials can cause stress shielding and product collapse due to the mismatch between their elastic modulus and human bone. The mechanical properties of polymer scaffolds themselves are not enough to match the mechanical properties of human autologous bone. In addition, there is increasing evidence that polymer and metal wear debris have the potential to dissolve bone in intervertebral discs and other artificial joints, and specific cases of osteolysis related to intervertebral disc replacement have begun to appear. After bioceramic bone repair materials are implanted in the body, a hydroxyapatite-like layer similar to the composition of bone tissue can be formed on their surface, and they are chemically bonded to bone tissue, thereby inducing ectopic osteogenesis. Among them, the degradation rate of ceramic materials such as hydroxyapatite (HA) and tricalcium phosphate (β-TCP) is not completely controllable, and their mechanical properties are somewhat different from those of living bones. They are usually used for non-load-bearing bones in the human body and are not suitable as intervertebral fusion materials. ZTA ceramics have become one of the most competitive materials for the preparation of orthopedic implants in load-bearing parts due to their good mechanical properties and biocompatibility. In order to improve the osteogenic properties of ZTA, active materials such as bioglass are usually added to it; however, the softening temperature of bioglass is more than 600°C lower than the sintering temperature of ZTA ceramics, and complex reactions or crystallization occur during the sintering process, which greatly reduces the mechanical properties of the final ceramic implant. Summary of the invention
[0005] In view of the shortcomings of the prior art, the first purpose of the present invention is to provide a ZTA ceramic intervertebral fusion device. The intervertebral fusion device provided by the present invention has the advantages of imitating human bone structure, high porosity, high strength, good biological activity, good bone induction performance, etc., and the mechanical properties of the intervertebral fusion device can be adjusted according to the patient's needs.
[0006] The second object of the present invention is to provide a method for preparing a ZTA ceramic intervertebral fusion cage.
[0007] The third object of the present invention is to provide an application of a ZTA ceramic intervertebral fusion cage.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] The present invention provides a ZTA ceramic intervertebral fusion device, which consists of a dense outer wall and a porous interior, wherein the porous interior has a gradient porous three-periodic minimal surface structure; the material of the ZTA ceramic intervertebral fusion device is a calcium magnesium silicate mineral / ZTA composite ceramic material.
[0010] The ZTA ceramic intervertebral fusion device provided by the present invention has a porous interior as the core structure of an artificial intervertebral disc, combined with a dense outer wall to form a complete bionic structure of an artificial intervertebral disc; the intervertebral fusion device provided by the present invention is a calcium magnesium silicate mineral / ZTA composite ceramic material, wherein ZrO2 toughened Al2O3 composite ceramic (ZTA) has excellent wear resistance, compression resistance and biocompatibility; the calcium magnesium silicate mineral bioceramic material can be used as a bioactive additive to enhance the bioactivity of ZTA and promote induced osteogenesis. At the same time, the melting point of the calcium magnesium silicate mineral is lower than the sintering temperature range of ZTA (1550-1650°C), so it can be used as a crystal sintering additive to improve the sintering performance of ZTA, reduce the sintering temperature, and increase the sintering density. The calcium magnesium silicate mineral / ZTA composite ceramic material enables the intervertebral fusion device to meet good mechanical properties and biocompatibility, while having good bioactivity to promote osteogenesis.
[0011] In a preferred embodiment, the thickness of the dense outer wall of the ZTA ceramic intervertebral fusion device is 0.25-0.5 mm.
[0012] The inventors found that when the wall thickness is 0.25-0.5 mm, the overall structural stress distribution is most uniform and the performance of the ZTA ceramic intervertebral fusion device is optimal. If the wall thickness is too large, the mechanical properties are too high and are not within the range of human bone mechanical properties. If the wall thickness is too small, the mechanical properties are low and do not meet the mechanical properties of human bone.
[0013] The diameter and height of the ZTA ceramic intervertebral fusion device can be specifically designed according to needs, such as a cylindrical structure with a diameter of 10 mm and a height of 5 mm.
[0014] In a preferred embodiment, the average porosity of the porous interior is 20% to 80%.
[0015] For intervertebral fusion devices, although the elastic modulus and compressive strength of the gradient porous bionic structure gradually decrease with the increase of total porosity, the mechanical properties can be regulated by the gradient change design of porosity and the regulation of magnesia feldspar content, so that the porosity of ZTA ceramic intervertebral fusion devices can reach 80%, which can meet the application requirements. Of course, if the porosity is too low, the ideal gradient distribution structure cannot be obtained. If the porosity is too high, the mechanical properties are reduced, and during the forming process, the exposure area is small and the release is difficult, which can easily lead to forming failure.
[0016] Further preferably, the porosity of the porous interior increases gradually from the central axis to the circumferential surface, wherein the porosity (P1) at the central axis is 30%-70%, the porosity (P2) at the circumferential surface is 50%-80%, and the average porosity is 50% to 70%.
[0017] The inventors found that when the radial inner and outer porosities are similar, the mechanical properties of the gradient porous bionic structure also tend to be homogeneous porous structures. However, natural bone is composed of low-porosity cortical bone and high-porosity cancellous bone, presenting an uneven gradient porous structure, and when the porosity of the mean structure is gradiently changed, a porous structure with multiple gradient changes is obtained, which has better mechanical properties than the mean pore structure, especially when the porosity P1 at the central axis of the radial gradient pore structure is controlled at 30%-70%, and the porosity P2 at the circumferential surface of the radial gradient pore structure is 50%-80%, from the inside to the outside, the porosity increases from P1 to P2, and the average porosity is controlled to be 50%-70%, a pore gradient distribution bionic structure similar to natural bone can be obtained, and mechanical and biological properties similar to natural bone can be obtained.
[0018] In a preferred embodiment, the porous internal structure is obtained by thickening the plane formed by the basic function equation of the D-type minimal surface, and the basic function equation of the D-type minimal surface is:
[0019] F(x,y,z)=sin(x)*sin(y)*sin(z)+sin(x)*cos(y)*cos(z)+cos(x)*siny)*cos(z)+cos(x)*cos(y)*sin(z)+C(x,y), where C(x,y)=k(x 2 +y 2 )+b, k is -0.0381~0, and b is 0.0238~0.7381.
[0020] The intervertebral fusion device provided by the present invention can control the size of the pore size by changing the values of k and b in the equation C(x,y). The inventors found that when k is -0.0381 to 0 and b is 0.0238 to 0.7381, the porosity of the porous interior presents the above-mentioned gradient porous structure, and the average porosity is controlled to be 50% to 70%. Therefore, the k value and the b value need to be effectively controlled. When the k value and the b value are controlled within the above range, a bionic structure with a pore gradient distribution similar to that of natural bone can be obtained, and at the same time, mechanical and biological properties similar to those of natural bone can be obtained.
[0021] In a preferred embodiment, in the ZTA ceramic intervertebral fusion device, the mass fraction of calcium magnesium silicate mineral is 2.5-30%, preferably 5-20%.
[0022] The inventors found that controlling the mass fraction of calcium magnesium silicate mineral within the above range will achieve the best final effect. If the added amount is too large, it will affect the stability of the slurry. At the same time, during sintering, due to the increase in the amount of high-temperature liquid phase of calcium magnesium silicate mineral, the liquid phase is fully sintered, causing the Al2O3 grains to grow abnormally, resulting in many micropores, resulting in reduced mechanical properties of the scaffold.
[0023] In a preferred embodiment, the calcium magnesium silicate mineral is selected from magnesia chalcedony (Ca2MgSi2O7), diopside (CaMgSi2O6), wollastonite (Ca3MgSi2O8), 2+ Mg 2+ )SiO3), preferably Ca2MgSi2O7. The inventors found that Ca2MgSi2O7, whose melting point is 150°C-250°C lower than the sintering temperature of ZTA ceramics, can be used as a crystal sintering aid to promote ZTA densification, and as a bioactive factor, it can induce osteoblast differentiation and promote bone tissue repair.
[0024] The present invention also provides a method for preparing a ZTA ceramic intervertebral fusion device, comprising preparing ceramic powder and photosensitive raw materials according to a designed ratio, mixing the materials to obtain ceramic slurry, adding the ceramic slurry into a photocuring printing device, performing photocuring printing according to a ZTA ceramic intervertebral fusion device model to obtain a ceramic blank, and degreasing and sintering the ceramic blank to obtain a ZTA ceramic intervertebral fusion device; the ceramic powder consists of ZrO2 powder, Al2O3 powder, and calcium magnesium silicate minerals.
[0025] In a preferred embodiment, the particle sizes of the ZrO2 powder, Al2O3 powder and calcium magnesium silicate mineral are all submicron.
[0026] The inventors found that when ZrO2 powder, Al2O3 powder, and calcium magnesium silicate mineral all have submicron particle sizes, the final composite material has the best performance. If the particle size is too small, agglomeration will occur, which is not conducive to dispersion in the ceramic slurry.
[0027] In a preferred embodiment, in the ceramic powder, the mass ratio of ZrO2 powder to Al2O3 powder is 1:3-6, preferably 1:3, and the mass fraction of calcium magnesium silicate mineral is 2.5%-30%, preferably 5-20%.
[0028] In a preferred embodiment, the photosensitive raw material comprises the following components by mass percentage: 1-5% Solsperse 41000, 0.1-3% Sago-8810, 0.1-3% Rad 25000, 0.1-3% TEGO foamex N, 0.1-3% polyethylene glycol (PEG200), 20-40% 1-hydroxycyclohexyl phenyl ketone (184), 20-40% trimethylolpropane triacrylate (TMPTA), 10-50% hexanediol diacrylate (HDDA), and 10-30% 2-hydroxyethyl acrylate (HEA).
[0029] The ceramic slurry in the present invention is a colloidal system composed of ceramic powder and photosensitive resin, and its rheological properties are mainly composed of the interaction force between particles (van der Waals force, electrostatic repulsion, steric hindrance effect) and Brownian motion. The inventor found that there are a large number of hydrophilic hydroxyl groups on the surface of Al2O3 and ZrO2 powders. When no dispersant is added, the free energy of the powder surface is too high, and the powder is prone to agglomeration. At the same time, since the HDDA+TMPTA+HEA resin system is an oily molecule, its wettability to Al2O3 and ZrO2 powders is poor, which will further aggravate the phenomenon of powder agglomeration. In view of the fact that UV light-curing resin is an organic system, the powder surface is not enough to generate Zeta potential, and the main stabilization mechanism of the ceramic slurry is the steric stabilization mechanism. Therefore, the present invention adds Solsperse 41000 as a dispersant to the ceramic slurry, changes the hydrophilicity of the surface of submicron Al2O3 and ZrO2 powders to hydrophobicity, and obtains a stable ceramic slurry by generating a steric hindrance effect. Sago-8810X is added as an anti-settling agent to give the slurry good thixotropic properties. After the shearing effect is removed, the weak cross-linking effect between the slurries is restored, and the viscosity recovers with appropriate hysteresis, so that it has good leveling and anti-sagging properties. Finally, the slurry returns to its original thixotropic state. With the synergy of the above components, a ceramic slurry with good dispersibility, good fluidity and high solid content can be obtained. At the same time, in the combination of the photosensitive resin of the present invention, 1-hydroxycyclohexyl phenyl ketone (184) is a photoinitiator. Under the irradiation of ultraviolet light with low energy density, a high-precision and high-performance photocured blank is prepared.
[0030] In addition, in order to improve the quality of the printed blank, the present invention further adds Rad2500 as a release agent, which can form an isolation film on the surface of the mold and the platform, making it convenient for the printed model to be separated from the platform. TEGO foamex N is used as a defoaming agent, which can quickly spread on the foam surface and penetrate quickly, so that the foam can quickly break and discharge the gas in the slurry to eliminate bubbles. Polyethylene glycol (PEG 200) is used as a plasticizer. When the plasticizer is mixed with the resin, the small molecules of the plasticizer will be inserted between the polymer molecular chains, weakening the attraction between the polymer molecular chains and increasing the distance between them. As a result, the possibility of polymer molecular chain movement is increased, the entanglement between polymer molecular chains is reduced, the plasticity is increased, and the mechanical properties of the scaffold can be enhanced.
[0031] In a preferred embodiment, the mixing is carried out under vacuum conditions, and the mixing process is: firstly mixing at 800-1200 rpm for 30s-2min, then mixing at 1200-2000 rpm for 3-5min, and finally mixing at 800-1200 rpm for 30s-2min. The inventors have found that the dispersion of the slurry obtained is optimal when stirring under the above conditions.
[0032] The present invention adopts a vacuum high-speed stirring process to prepare a ceramic slurry with a high solid content (50-55 vol%).
[0033] In a preferred embodiment, the solid content of the ceramic slurry is 50-55 vol%. In the present invention, the solid content of the ceramic slurry refers to the total volume percentage of the ceramic powder in the ceramic slurry.
[0034] In a preferred embodiment, the process of obtaining the ZTA ceramic intervertebral fusion cage model is as follows: first, a plane model is formed by the basic function equation of the D-type minimal surface, then the plane is thickened to obtain a porous interior, and then a dense outer wall is set on the porous interior surface to obtain the ZTA ceramic intervertebral fusion cage model. The basic function equation is:
[0035] F(x,y,z)=sin(x)*sin(y)*sin(z)+sin(x)*cos(y)*cos(z)+cos(x)*sin(y)*cos(z)+cos(x)*cos(y)*sin(z)+C(x,y), where C(x,y)=k(x 2 +y 2 )+b, k is -0.0381~0, and b is 0.0238~0.7381.
[0036] In a preferred embodiment, the parameters of the light-curing printing are: the exposure energy density is 0.125 to 0.711 J / cm 2 , the slice thickness is 30 to 60 μm.
[0037] In the present invention, the process parameters are precisely controlled within the above range to ensure that the designed pores in the model are consistent and high-precision ceramic blanks can be obtained in a controllable manner. It can be seen that the process window of the present invention is small. This is because the inventors found that the scattering of ultraviolet light by powder particles in the ceramic slurry will seriously reduce the forming accuracy of the aperture, resulting in a significant deviation of the processed pore structure from the model design. When the exposure energy is too high, the aperture size is lower than the design value, and even blockage occurs; when the exposure energy is too low, the interlayer bonding strength is low, and even the stacking manufacturing fails. The present invention uses a single-layer solidification thickness experiment to establish the relationship between the photocuring forming parameter (surface exposure energy density) and the solidification thickness, determines the forming parameter that is 1.5 to 2 times thicker than the layer thickness, and preliminarily determines the process window; on this basis, the relationship between the surface exposure energy density, exposure time, layer thickness and additional scattering width is established by using the precision model test experiment, and the minimum energy density parameter that can process the precision model is selected as the optimal process parameter, that is, the manufacturing error of the precision model formed is small and the precision is the highest.
[0038] In a preferred embodiment, the degreasing is performed in a vacuum environment, the degreasing temperature is 400-600° C., and the degreasing time is 2500-3000 min.
[0039] In a preferred embodiment, the sintering temperature is 100-300° C. lower than the ZTA sintering temperature, the sintering temperature is 0-200° C. lower than the melting point of calcium magnesium silicate mineral, and the sintering time is 1-3 hours.
[0040] The inventor unexpectedly discovered that by adding calcium magnesium silicate minerals, the sintering temperature is controlled at 0-200°C below the melting point of calcium magnesium silicate minerals, which is 100°C-300°C lower than the sintering temperature of ZTA. However, calcium magnesium silicate can be used as a crystal sintering aid to promote the densification of ZTA ceramics at this temperature. Of course, when the temperature is controlled within this range, the calcium magnesium silicate mineral does not melt and can act as a bioactive factor to induce osteoblast differentiation, promote bone tissue repair, and enhance the bioactivity of ZTA ceramics.
[0041] Therefore, the temperature of the present invention must also be effectively controlled. If the temperature is too low, sintering and densification cannot be achieved. If the temperature is too high, the osteoinductive properties of the ZTA ceramic will be reduced.
[0042] Further preferably, the sintering temperature is 1300-1400°C, and the sintering time is 1-3h. The inventors found that when sintering, the calcium magnesium silicate mineral added is Ca2MgSi2O7 (melting point 1400°C), which is 150-250°C lower than the ZTA sintering temperature. When the sintering temperature is 0-150°C lower than the melting point of Ca2MgSi2O7, the resulting ZTA ceramic has the highest degree of densification and the best biological activity.
[0043] Further preferably, the sintering process is to first heat the temperature to 400-500°C at a heating rate of 0.5-1°C / min, keep it warm for 2-6h, then heat the temperature to 1300-1400°C at a heating rate of 5-10°C / min, keep it warm for 1-3h, and cool to room temperature with the furnace.
[0044] The present invention also provides an application of a ZTA ceramic intervertebral fusion device, wherein the ZTA ceramic intervertebral fusion device is used as an artificial intervertebral disc bionic implant.
[0045] Principles and advantages
[0046] ①Structural design of intervertebral fusion cage
[0047] The present invention designs a bionic intervertebral fusion device with high porosity, high permeability and good mechanical properties by regulating the structural parameters of the D-type minimal surface. The model adjusts the porosity change by regulating the structural parameters to design and prepare an intervertebral fusion device with regulated mechanical properties. The high porosity can provide a channel for bone and blood vessel growth.
[0048] ② Selection of stent materials
[0049] The intervertebral fusion device provided by the present invention is a calcium magnesium silicate mineral / ZTA composite ceramic material. In the prior art, the intervertebral fusion device used in intervertebral disc replacement surgery is made of titanium alloy material. The difference in elastic modulus between the titanium alloy and the vertebral body easily causes stress shielding, resulting in the failure of the intervertebral fusion device and the vertebral body to grow closely together; in addition, titanium alloy does not have the ability to induce osteogenesis, and the abrasive particles produced by wear will cause inflammation at the lesion site. In addition, bioceramic materials are currently the mainstream bone repair materials, but the common HA and β-TCP can only be applied to non-load-bearing bones of the human body, and the mechanical strength is not high, which greatly limits the application scope of the stent. The ZrO2 toughened Al2O3 composite ceramic (ZTA) used in this stent is a bioceramic material with great potential for implants in orthopedic load-bearing parts. The ZTA bioceramic exhibits excellent mechanical properties and biological activity, and its relative density, Vickers hardness and fracture toughness are as high as 99.09%, 16.66GPa and 6.88MPa·m respectively. 1 / 2 . In addition, bone marrow mesenchymal stem cells show strong adhesion and proliferation ability on the surface of the ZTA ceramic, and can be well used in various bone repair scenarios. The melting point of calcium magnesium silicate minerals is 150℃~250℃ lower than the sintering temperature of ZTA ceramics. As a crystal sintering aid, it promotes the densification of ZTA. At the same time, as a bioactive factor, it can induce osteoblast differentiation, promote bone tissue repair, and achieve mechanical property regulation by regulating the content of calcium magnesium silicate minerals.
[0050] ③Choice of preparation method
[0051] Common processing methods for intervertebral fusion devices are casting or injection molding, which cannot achieve personalized customization; 3D printing technology can process any complex structure and is suitable for intervertebral disc replacement surgery. However, high-melting-point bioceramics are prone to cracking under rapid cooling / heating conditions, and cannot be processed using the laser selective melting technology commonly used for titanium alloys. This project is based on ceramic slurry and innovatively uses light-curing 3D printing technology to form a gradient structure intervertebral fusion device, and obtains a personalized bionic intervertebral fusion device after high-temperature sintering.
[0052] Under the synergistic effect of the above structure, materials and processes, the intervertebral fusion device provided by the present invention has a dense outer layer of 0.25-0.5mm, a gradient porous inner layer with an average porosity of 50%-70%, a pore gradient interpolation of 20-50%, a compressive strength of 134.31-197.54MPa, and an elastic modulus of 5.407-6.842GPa, which meets the requirements of human bone mechanical strength (elastic modulus of 5.4-15.6GPa, compressive strength of 130-163MPa) BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 Controlling k and b values to obtain structural models of porous interiors with different porosities
[0054] Figure 2 Schematic diagram of preparation method
[0055] Figure 3 Physical pictures of structures with different porosity
[0056] Figure 4 Gradient porous interbody fusion cage DETAILED DESCRIPTION
[0057] The printing devices in the following embodiments are all CeraBuilder 60S industrial-grade high-performance ceramic 3D printers produced by Wuhan Intailai Laser Technology Co., Ltd.
[0058] Example 1
[0059] Design of intervertebral fusion cage model:
[0060] First, a plane model is formed by the basic function equation of the D-type minimal surface, and then the plane is thickened and a dense outer layer is added to form a gradient porous structure with a diameter of 10 mm and a height of 5 mm. The basic function equation is:
[0061] F(x,y,z)=sin(ax)*sin(ay)*sin(az)+sin(ax)*cos(ay)*cos(az)+cos(ax)*sin(ay)*cos(a
[0062] z)+cos(ax)*cos(ay)*sin(az)+C(x,y), where C(x,y)=k(x 2 +y 2 )+b, where k=-0.01896,
[0063] b=0.238, the porosity (P1) at the central axis of the radial gradient pore structure is 40%, the porosity (P2) at the circumferential surface is 60%, the average porosity is 50%, and the wall thickness is 0.5 mm. Gradient porous structure model.
[0064] Composition of ceramic slurry:
[0065] The photosensitive raw materials were prepared, calculated by mass percentage: Solsperse 41000 10.24%, Sago-8810 1.46%, Rad 2550 1.46%, TEGO foamex N 1.46%, polyethylene glycol (PEG 200) 4.14%, trimethylolpropane triacrylate (TMPTA) 24.86%, hexanediol diacrylate (HDDA) 33.15%, 2-hydroxyethyl acrylate (HEA) 20.72%, and 1-hydroxycyclohexyl phenyl ketone (184) 2.49%.
[0066] 100g of ceramic powder, the mass ratio of ZrO2 powder to Al2O3 powder is 1:3, and the mass fraction of Ca2MgSi2O7 powder in the ceramic powder is 5%.
[0067] The solid content of the ceramic slurry is 50 vol%
[0068] Preparation of ceramic slurry:
[0069] Ceramic powder and photosensitive raw materials were mixed under vacuum conditions. The mixing process was first at 800 rpm for 30 seconds, then at 1800 rpm for 3 minutes, and finally at 800 rpm for 30 seconds to prepare a ceramic slurry with a solid content of 45 vol%. The ceramic slurry was then poured into the material tank. After the model was imported into the printer, the solid content was 0.286 J / cm 2 The photocuring was performed under the conditions of exposure power density and slice thickness of 50 μm.
[0070] The material was placed in a vacuum muffle furnace for debinding, and the temperature was gradually increased from 0°C to 600°C. The sintering process increased the temperature to 200°C at a rate of 1°C / min, and then increased the temperature to 1350°C at a rate of 5°C / min, and kept at that temperature for 1h, and then cooled to room temperature with the furnace to obtain an artificial intervertebral disc scaffold.
[0071] The porosity of the scaffold is 50%, and the compressive strength and elastic modulus of the scaffold are 171.43MPa and 4.39GPa respectively. The CCK8 results show that the ceramic has good cell compatibility, and the RT-PCR experiment shows better gene expression.
[0072] Example 2
[0073] Design of intervertebral fusion cage model:
[0074] First, a plane model is formed by the basic function equation of the D-type minimal surface, and then the plane is thickened, and then a dense layer is added to the outer wall to obtain an artificial intervertebral disc stent model. The basic function equation is F(x,y,z)=sin(ax)*sin(ay)*sin(az)+sin(ax)*cos(ay)*cos(az)+cos(ax)*sin(ay)*cos(az)+cos(ax)*cos(ay)*sin(az)+C(x,y), where C(x,y)=k(x 2 +y 2 )+b, where k=-0.0048, b=0.5, the porosity (P1) at the central axis of the radial gradient pore structure is 50%, and the porosity (P2) at the circumferential surface is 70%, the average porosity is 60%, and the wall thickness is 0.25mm. Gradient porous structure model.
[0075] Composition of ceramic slurry:
[0076] The photosensitive raw materials were prepared, calculated by mass percentage: Solsperse 41000 10.24%, Sago-8810 1.46%, Rad 2550 1.46%, TEGO foamex N 1.46%, polyethylene glycol (PEG 200) 4.14%, trimethylolpropane triacrylate (TMPTA) 24.86%, hexanediol diacrylate (HDDA) 33.15%, 2-hydroxyethyl acrylate (HEA) 20.72%, 1-hydroxycyclohexyl phenyl ketone (184) 2.49%,
[0077] Ceramic powder 100g, the mass ratio of ZrO2 powder to Al2O3 powder is 1:3, and the mass fraction of Ca2MgSi2O7 powder in the ceramic powder is 10%.
[0078] The solid content of the ceramic slurry is 50 vol%
[0079] Preparation of ceramic slurry:
[0080] Ceramic powder and photosensitive raw materials were mixed under vacuum conditions. The mixing process was first at 800 rpm for 30 seconds, then at 1800 rpm for 3 minutes, and finally at 800 rpm for 30 seconds to prepare a ceramic slurry with a solid content of 45 vol%. The ceramic slurry was then poured into the material tank. After the model was imported into the printer, the solid content was 0.286 J / cm 2 The photocuring was performed under the conditions of exposure power density and slice thickness of 50 μm.
[0081] Place in a vacuum muffle furnace for debinding, and gradually increase the temperature from 0°C to 600°C. In the sintering process, the temperature is increased to 200°C at a rate of 1°C / min, and then to 1400°C at a rate of 5°C / min, and kept at this temperature for 1h, and then cooled to room temperature with the furnace to obtain an artificial intervertebral disc scaffold.
[0082] The porosity of the scaffold is 60%, and the compressive strength and elastic modulus of the scaffold are 140.57MPa and 4.5GPa respectively. The CCK8 results show that the ceramic has good cell compatibility, and the RT-PCR experiment shows better gene expression.
[0083] Example 3
[0084] Design of artificial intervertebral disc stent model:
[0085] First, a plane model is formed by the basic function equation of the D-type minimal surface, and then the plane is thickened, and then a dense layer is added to the outer wall to obtain an artificial intervertebral disc stent model. The basic function equation is F(x,y,z)=sin(ax)*sin(ay)*sin(az)+sin(ax)*cos(ay)*cos(az)+cos(ax)*sin(ay)*cos(az)+cos(ax)*cos(ay)*sin(az)+C(x,y), where C(x,y)=k(x 2 +y 2 )+b, where k=-0.01912, b=0.74, the porosity (P1) at the central axis of the radial gradient pore structure is 60%, the porosity (P2) at the circumferential surface is 80%, the average porosity is 70%, and the wall thickness is 0.5 mm. Gradient porous structure model.
[0086] Composition of ceramic slurry:
[0087] The photosensitive raw materials were prepared, calculated by mass percentage: Solsperse 41000 10.24%, Sago-8810 1.46%, Rad 2550 1.46%, TEGO foamex N 1.46%, polyethylene glycol (PEG 200) 4.14%, trimethylolpropane triacrylate (TMPTA) 24.86%, hexanediol diacrylate (HDDA) 33.15%, 2-hydroxyethyl acrylate (HEA) 20.72%, and 1-hydroxycyclohexyl phenyl ketone (184) 2.49%.
[0088] Ceramic powder 100g, the mass ratio of ZrO2 powder to Al2O3 powder is 1:3, and the mass fraction of Ca2MgSi2O7 powder in the ceramic powder is 20%.
[0089] The solid content of the ceramic slurry is 50 vol%
[0090] Preparation of ceramic slurry:
[0091] Ceramic powder and photosensitive raw materials were mixed under vacuum conditions. The mixing process was first at 800 rpm for 30 seconds, then at 1800 rpm for 3 minutes, and finally at 800 rpm for 30 seconds to prepare a ceramic slurry with a solid content of 45 vol%. The ceramic slurry was then poured into the material tank. After the model was imported into the printer, the solid content was 0.286 J / cm 2 The photocuring was performed under the conditions of exposure power density and slice thickness of 50 μm.
[0092] Place in a vacuum muffle furnace for debinding, and gradually increase the temperature from 0°C to 600°C. In the sintering process, the temperature is increased to 200°C at a rate of 1°C / min, and then to 1400°C at a rate of 5°C / min, and kept at this temperature for 1h, and then cooled to room temperature with the furnace to obtain an artificial intervertebral disc scaffold.
[0093] The porosity of the scaffold is 70%, and the compressive strength and elastic modulus of the scaffold are 135.33MPa and 3.54GPa respectively. The CCK8 results show that the ceramic has good cell compatibility, and the RT-PCR experiment shows that it has a significant effect on bone formation.
[0094] Comparative Example 1:
[0095] The other conditions are the same as those in Example 1, except that the k value in the basic function equation is set to -0.0571 and the b value is set to 0.7381, and a homogeneous structure model is obtained in which the porosity at the central axis is 20% and the porosity at the circumferential surface of the radial gradient pore structure is 80%, and the average porosity is still 50%. The mechanical properties of the obtained ZTA ceramic intervertebral fusion device have a compressive strength of 218.23 MPa, which is quite different from the mechanical properties of human bone.
[0096] Comparative Example 2
[0097] Other conditions were the same as those in Example 1, except that the wall thickness was 0.75 mm. The compressive strength of the obtained ZTA ceramic intervertebral fusion device was 248.67 MPa, which was quite different from the mechanical properties of human bones.
[0098] Comparative Example 3
[0099] Other conditions were the same as those in Example 1, except that the exposure energy density was set to 0.891 J / cm 2 This causes excessive internal stress in the ceramic during the printing process and cracks in the model during the degreasing and sintering process.
[0100] Comparative Example 4
[0101] Other conditions were the same as those in Example 1, except that the sintering temperature was set to 1500° C. The resulting ZTA ceramic intervertebral fusion cage had poor osteoinduction performance in the RT-PCR experiment.
[0102] Comparative Example 5
[0103] Other conditions were the same as those in Example 1, except that the mass fraction of Ca2MgSiO7 in the ceramic powder was 1.25%. The resulting ZTA ceramic intervertebral fusion cage had poor osteoinduction performance in the RT-PCR experiment.
Claims
1. A ZTA ceramic intervertebral fusion cage, characterized in that: The ZTA ceramic intervertebral fusion device consists of a dense outer wall and a porous interior, wherein the porous interior has a gradient porous three-periodic minimal surface structure; the material of the ZTA ceramic intervertebral fusion device is a calcium magnesium silicate mineral / ZTA composite ceramic material.
2. The ZTA ceramic intervertebral fusion cage according to claim 1, characterized in that: The thickness of the dense outer wall of the ZTA ceramic intervertebral fusion device is 0.25 to 0.5 mm; The average porosity of the porous interior is 20% to 80%.
3. A ZTA ceramic intervertebral fusion cage according to claim 1 or 2, characterized in that: The porosity of the porous interior increases gradually from the central axis to the circumferential surface, wherein the porosity at the central axis is 30%-70%, the porosity at the circumferential surface is 50%-80%, and the average porosity is 50%-70%; The structure of the porous interior is obtained by thickening the plane formed by the basic function equation of the D-type minimal surface. The basic function equation of the D-type minimal surface is: F(x,y,z)=sin(x)*sin(y)*sin(z)+sin(x)*cos(y)*cos(z)+cos(x)*siny)*cos(z)+cos(x)* cos(y)*sin(z)+C(x,y), where C(x,y)=k(x 2 +y 2 )+b, k is -0.0381~0, and b is 0.0238~0.7381.
4. A ZTA ceramic intervertebral fusion cage according to claim 1 or 2, characterized in that: In the ZTA ceramic intervertebral fusion device, the mass fraction of calcium magnesium silicate mineral is 2.5-30%, and the calcium magnesium silicate mineral is selected from at least one of magnesia pyroxene, diopside, mordenite, and wollastonite.
5. The method for preparing a ZTA ceramic intervertebral fusion device according to any one of claims 1 to 4, characterized in that: Ceramic powder and photosensitive raw material are prepared according to the designed proportion, and ceramic slurry is obtained by mixing. The ceramic slurry is added into a light-curing printing device, and light-curing printing is performed according to a ZTA ceramic intervertebral fusion device model to obtain a ceramic blank. The ceramic blank is degreased and sintered to obtain a ZTA ceramic intervertebral fusion device. The ceramic powder consists of ZrO2 powder, Al2O3 powder, and calcium-magnesium silicate minerals.
6. The method for preparing a ZTA ceramic intervertebral fusion cage according to claim 5, characterized in that: The particle sizes of the ZrO2 powder, Al2O3 powder and calcium magnesium silicate mineral are all submicron; In the ceramic powder, the mass ratio of ZrO2 powder to Al2O3 powder is 1:3-6, and the mass fraction of calcium magnesium silicate mineral is 2.5%-30%; The photosensitive raw material is composed of the following components by mass percentage: Solsperse 41000 1-5%, Sago-8810 0.1-3%, Rad 25000 0.1-3%, TEGO foamex N 0.1-3%, polyethylene glycol 0.1-3%, 1-hydroxycyclohexyl phenyl ketone 20-40%, trimethylolpropane triacrylate 20-40%, hexanediol diacrylate 10-50%, and 2-hydroxyethyl acrylate 10-30%.
7. The method for preparing a ZTA ceramic intervertebral fusion cage according to claim 5, characterized in that: The mixing is carried out under vacuum conditions, and the mixing process is: firstly mixing at 800-1200 rpm for 30s-2min, then mixing at 1200-2000 rpm for 3-5min, and finally mixing at 800-1200 rpm for 30s-2min; In the ceramic slurry, the solid content is 50-55 vol%.
8. The method for preparing a ZTA ceramic intervertebral fusion cage according to claim 5, characterized in that: The acquisition process of the ZTA ceramic intervertebral fusion device model is as follows: first, a plane model is formed by the basic function equation of the D-type minimal surface, and then the plane is thickened to obtain a porous interior, and then a dense outer wall is set on the porous interior surface to obtain the ZTA ceramic intervertebral fusion device model. The basic function equation is F(x,y,z)=sin(x)*sin(y)*sin(z)+sin(x)*cos(y)*cos(z)+cos(x)*sin(y)*cos(z)+cos(x)*cos(y)*sin(z)+C(x,y), where C(x,y)=k(x 2 +y 2 )+b, k is -0.0381~0, and b is 0.0238~0.7381.
9. The method for preparing a ZTA ceramic intervertebral fusion cage according to claim 5, characterized in that: The parameters of the photocuring printing are: the exposure energy density is 0.125-0.711 J / cm 2 , the slice thickness is 30-60 μm; The degreasing is carried out in a vacuum environment, the degreasing temperature is 400-600° C., and the degreasing time is 2500-3000 min; The sintering temperature is 100-300° C. lower than the ZTA sintering temperature and 0-200° C. lower than the melting point of calcium magnesium silicate minerals. The sintering time is 1-3 hours.
10. The use of a ZTA ceramic intervertebral fusion device according to any one of claims 1 to 4, characterized in that: The ZTA ceramic intervertebral fusion cage is used as an artificial intervertebral disc bionic implant.
Citation Information
Patent Citations
Components for fusing vertebral bodies
CN107072795A
Preparation method of ZTA (zirconia toughened alumina) wear-resistant ceramic
CN109336565A
Preparation method of light curing 3D printing ceramic bone scaffold
CN109865157A
Gradient porous cervical interbody fusion cage and design method thereof
CN110179570A
3D printed high-strength ZTA ceramic substrate material and preparation process
CN111777408A
Cited By
Interbody fusion cage and manufacturing method thereof
CN122272249A